Pembelajaran Al-Qurâ€™an Metode â€œWafaâ€: Sebuah Inovasi Metode Pembelajaran Al-Qurâ€™an dengan Optimalisasi Otak Kiri dan Otak Kanan - Ratnawati, Siti Rohmaturrosyidah; Solihah, Imrotus (ACIECE, 2017)
This study examines "WAFA" Qurâ€™anic learning method and its relationship with Roger Sperryâ€™sBrain Hemisphere Theory and Learning Styles (Visual, Auditorial, Kinesthetic/VAK). Withliterature research, the research result indicates that WAFA method has a comprehensive andfun learning system of the Qur'an. WAFA is an al-Qur'an learning method innovation whichpackaged by left and right brain optimization and it also accommodates the three kinds oflearning styles of children. It can be seen from the teaching materials which arranged insequence letters that are packaged in a unique concept of combined words, equipped withinteresting pictures, and colorful. In addition, the comprehensiveness of WAFA method can alsobe seen from TANDUR learning strategies used in the learning process which can make theQur'an learning process very lively, easy and fun. The use of â€˜hijazâ€™ song and body movements inâ€œtilawahâ€ and â€œtahfidzâ€ are also the form of WAFAâ€™s comprehensiveness in optimizing both theleft brain and right brain of children.